A full life reflections at ninety - Carter, Jimmy (New York Simon & Schuster, 2015)
At ninety, Jimmy Carter reflects on his public and private life with a frankness that is disarming. He adds detail and emotion about his youth in rural Georgia that he described in his magnificent An Hour Before Daylight. He writes about racism and the isolation of the Carters. He describes the brutality of the hazing regimen at Annapolis, and how he nearly lost his life twice serving on submarines and his amazing interview with Admiral Rickover. He describes the profound influence his mother had on him, and how he admired his father even though he didn?t emulate him. He admits that he decided to quit the Navy and later enter politics without consulting his wife, Rosalynn, and how appalled he is in retrospect.
Includes index.
Keywords: Carter, Jimmy, 1924-